Learning transformation with digital technology: The era of education 4.0 - Khotimah, Khusnul; Anam, Khoirul; Afifah, Muthiah; Handayani, Ratih (Arshaka: Social Sciences and Education, 2025)
This study explores the application of digital technology in education by teachers in Indonesia and its impact on learning quality. Using qualitative research methods, in-depth interviews were conducted with 8 teachers who integrate digital tools such as Canva, Quizizz, ChatGPT, Google, and YouTube in their lessons. The findings reveal that digital technologies enhance the creation of engaging and interactive learning materials, significantly boosting student engagement and motivation. Tools like Quizizz and YouTube have proven effective in deepening students' understanding of the material, while ChatGPT provides immediate feedback. However, challenges such as limited infrastructure, technological access, and students' digital skills gap remain. This study emphasizes the need for educational policies that promote equal access to technology and suggests more comprehensive training for both teachers and students to optimize the use of digital tools in education. The findings contribute to the ongoing discourse on digital transformation in the era of Education 4.0.